DAMPAK PERKEBUNAN KELAPA SAWIT RAKYAT TERHADAP PENDAPATAN WILAYAH DESA (PDRB) DI PROVINSI JAMBI - Mara, Armen; Fitri, Yanuar (Jurnal AGRISEP, 2013)
Smallholder oil palm estate in Jambi Province is growing. Some indicators are land development, production, and employment. Smallholder oil palm estate can be a major driver of the economy so that the country can move other economic sectors, such as trade, transport, electricity and gas, manufacture small industrial and other sectors, which in turn increases the income of the village as a whole. This study aimed to determine (1) the development of oil palm estate seen from land, production, and employment in the province of Jambi (2) Impact of smallholder oil palm estate against Gross Regional Domestic Product Villages in Jambi Province. The research method used in this study is a survey method. This method of research was done deductively, by conducting an analysis of the object. Data were collected from primary sources and secondary sources. The development of oil palm plantations quantitatively analyzed descriptively. To determine whether the development of oil palm plantations had such an impact is determined by the formula LQ (Location Quotient) and the magnitude of the impact made by Formula ME (multiplier effect). To determine the value of LQ and ME the sample villages can be determined that a major driver of the sector (Prime mover sector) in the village economy. These results indicate that oil palm plantations have grown rapidly both views of land, production, and employment. Oil palm plantations have an impact on the income of the people of the village, where 9 of 20 samples villages have values LQ>1 with the average ME value was 1.4107, which means that any increase in palm oil revenue amounted toRp1, -it will be able to increase the income of the region village as a whole amounted to1.4107times. The impact is especially true of the sub-sectors of trade, transport sub-sector, and electricity and gas sub-sector. The impact is small relative to the manufacturing sector.